Information and human values - Fleischmann, Kenneth R. ([San Rafael, California] : Morgan & Claypool Publishers, 2014)
This book seeks to advance our understanding of the relationship between information and human values by synthesizing the complementary but typically disconnected threads in the literature, reflecting on my 15 years of research on the relationship between information and human values, advancing our intellectual understanding of the key facets of this topic, and encouraging further research to continue exploring this important and timely research topic.
Why human values? -- Approaches to understanding values -- Education and human values -- Technology and human values -- Communication and human values -- Synthesis : reconsidering information and human values -- A research agenda for information and human values.
Includes abstract.
Includes bibliographical references (pages 71-81).
Keywords: Values; Education -- Moral and ethical aspects; Computer simulation -- Moral and ethical aspects; Information technology -- Moral and ethical aspects; Content analysis (Communication).